Efficient access to alkynylated quinalizinones via the gold(I)-catalyzed aminoalkynylation of alkynes - Shinde, Popat S.; Shaikh, Aslam C.; Patil, Nitin T. (Chemical Communications, 2016)
The gold-catalyzed aminoalkynylation of alkynes for the synthesis of quinalizinones is reported. For instance, the reaction of pyridinoalkynes with 1-[(triisopropylsilyl)-ethynyl]-1,2-benziodoxol-3(1H)-one (TIPS-EBX) in the presence of a catalytic amount of AuCl at 50 8C afforded alkynylated quinalizinones in 57-87% yields.